"Making Space": How Novice Teachers Create Opportunities for Equitable Sense-Making in Elementary Science. (January 2020) - Haverly, Christa; Calabrese Barton, Angela; Schwarz, Christina V.; Braaten, Melissa
Scholarly calls to reform science education for all students emphasize scientific sense-making. Despite the importance of sense-making, few strategies exist to help novice teachers learn to notice and respond equitably to students' scientific sense-making in elementary science. In this article, we report on a qualitative case study in which we investigated sense-making moments that occurred when novice teachers facilitated classroom discussions. Findings suggest that when novice teachers made space in class discussions for sense-making—for example, by trying different responses to clarify student ideas or waiting before responding to figure out next steps—this expanded opportunities for shared epistemic authority; however, novices did not often recognize these moments as productive for sense-making. Findings also suggest that novice teachers may benefit from support to help them develop their abilities to notice, interpret, and respond equitably to students' scientific sense-making in class discussions.